The MOCAST+ Study on a Quantum Gradiometry Satellite Mission with Atomic Clocks - Federica Migliaccio; Mirko Reguzzoni; Gabriele Rosi; Carla Braitenberg; Guglielmo Maria Tino; Fiodor Sorrentino; Sergio Mottini; Lorenzo Rossi; Öykü Koç; Khulan Batsukh; Tommaso Pivetta; Alberto Pastorutti; et al. (Surveys in Geophysics, 2023)
In the past twenty years, satellite gravimetry missions have successfully provided data for the determination of the Earth static gravity field (GOCE) and its temporal variations (GRACE and GRACE-FO). In particular, the possibility to study the evolution in time of Earth masses allows us to monitor global parameters underlying climate changes, water resources, flooding, melting of ice masses and the corresponding global sea level rise, all of which are of paramount importance, providing basic data on, e.g. geodynamics, earthquakes, hydrology or ice sheets changes. Recently, a large interest has developed in novel technologies and quantum sensing, which promise higher sensitivity, drift-free measurements, and higher absolute accuracy for both terrestrial surveys and space missions, giving direct access to more precise long-term measurements. Looking at a time frame beyond the present decade, in the MOCAST+ study (MOnitoring mass variations by Cold Atom Sensors and Time measures) a satellite mission based on an “enhanced” quantum payload is proposed, with cold atom interferometers acting as gravity gradiometers, and atomic clocks for optical frequency measurements, providing observations of differences of the gravitational potential. The main outcomes are the definition of the accuracy level to be expected from this payload and the accuracy level needed to detect and monitor phenomena identified in the Scientific Challenges of the ESA Living Planet Program, in particular Cryosphere, Ocean and Solid Earth. In this paper, the proposed payload, mission profile and preliminary platform design are presented, with end-to-end simulation results and assessment of the impact on geophysical applications.

Gravity Field Recovery and Error Analysis for the MOCASS Mission Proposal Based on Cold Atom Interferometry - Mirko Reguzzoni; Federica Migliaccio; Khulan Batsukh (Pure and Applied Geophysics, 2021)
Satellite missions providing data for a continuous monitoring of the Earth gravity field and its changes are fundamental to study climate changes, hydrology, sea level changes, and solid Earth phenomena. GRACE-FO (Gravity Recovery and Climate Experiment Follow-On) mission was launched in 2018 and NGGM (Next Generation Gravity Mission) studies are ongoing for the long-term monitoring of the time-variable gravity field. In recent years, an innovative mission concept for gravity measurements has also emerged, exploiting a spaceborne gravity gradio-meter based on cold atom interferometers. In particular, a team of researchers from Italian universities and research institutions has proposed a mission concept called MOCASS (Mass Observation with Cold Atom Sensors in Space) and conducted the study to investigate the performance of a cold atom gradiometer on board a low Earth orbiter and its impact on the modeling of different geophysical phenomena. This paper presents the analysis of the gravity gradient data attainable by such a mission. Firstly, the mathematical model for the MOCASS data processing will be described. Then numerical simulations will be presented, considering different satellite orbital altitudes, pointing modes and instrument configurations (single-arm and double-arm); overall, data were simulated for twenty different observation scenarios. Finally, the simulation results will be illustrated, showing the applicability of the proposed concept and the improvement in modeling the static gravity field with respect to GOCE (Gravity Field and Steady-State Ocean Circulation Explorer).

The gravimetric contribution to the Moho estimation in the presence of vertical density variations - Mirko Reguzzoni; Daniele Sampietro; Lorenzo Rossi (Rendiconti Lincei. Scienze Fisiche e Naturali, 2020)
The Moho surface, namely the density discontinuity between crust and mantle, is traditionally studied by seismic methods. However, gravity information can contribute to the Moho estimation and, more generally, to the crustal modeling. The contribution is twofold. First, gravimetry generally provides observations with much lower errors than those implied by the mass density uncertainty and other geophysical assumptions. This means that it can be used to validate existing Moho and/or crustal models by forward modeling. Second, gravity inversion is able to provide diffused (not localized) information on the mass distribution, both regionally and globally (thanks to dedicated satellite gravity missions). However, this information is weak due to its intrinsic ill-posedness. This means that it can be used to correct and spatially interpolate existing models, and to complement seismic, magnetic and geological information to create new models. In this work, the problem of estimating the Moho surface by gravity inversion assuming a two-layer model with lateral and vertical density variations is treated at a regional level. The approach consists in linearizing the forward modeling around a reference Moho at a constant depth and then inverting it through a Wiener filter. This is standard in case of two layers with homogeneous density distributions (or with lateral density variations), while it requires some additional considerations and algorithm modifications in case of vertical density variations. The basic idea is to “condensate” the masses inside the Moho undulation on the reference surface used for the linearization, thus requiring the setup of an iterative procedure. A strategy to introduce seismic information into this inversion procedure is proposed too, with the aim of improving the a priori density modeling. A closed loop test is presented for the algorithm assessment, showing the improvement with respect to a standard approach and the capability of the proposed algorithm to reconstruct the originally simulated Moho undulation by also fitting the gravity and seismic data at a level that is consistent with their observation noise.

MOCASS: A Satellite Mission Concept Using Cold Atom Interferometry for Measuring the Earth Gravity Field - Federica Migliaccio; Mirko Reguzzoni; Khulan Batsukh; Guglielmo Maria Tino; Gabriele Rosi; Fiodor Sorrentino; Carla Braitenberg; Tommaso Pivetta; Dora Francesca Barbolla; Simona Zoffoli (Surveys in Geophysics, 2019)

IRG2018: A regional geoid model in Iran using Least Squares Collocation - Sabah Ramouz; Yosra Afrasteh; Mirko Reguzzoni; Abdolreza Safari; Abdoreza Saadat (Studia Geophysica et Geodaetica, 2019)

goGPS: open-source MATLAB software - Antonio M. Herrera; Hendy F. Suhandri; Eugenio Realini; Mirko Reguzzoni; M. Clara de Lacy (GPS Solutions, 2016)

GECO: a global gravity model by locally combining GOCE data and EGM2008 - Maddalena Gilardoni; Mirko Reguzzoni; Daniele Sampietro (Studia Geophysica et Geodaetica, 2016)

The Earth gravity field in the time of satellites - Riccardo Barzaghi; Federica Migliaccio; Mirko Reguzzoni; Alberta Albertella (Rendiconti Lincei. Scienze Fisiche e Naturali, 2015)

Integrating low-cost RTK positioning services with a web-based track log management system - Daisuke Yoshida; Eugenio Realini; Mirko Reguzzoni; Venkatesh Raghavan (Applied Geomatics, 2013)

The height datum problem and the role of satellite gravity models - Andrea Gatti; Mirko Reguzzoni; Giovanna Venuti (Journal of Geodesy, 2013)

Real-time cycle slip detection in triple-frequency GNSS - Maria Clara de Lacy; Mirko Reguzzoni; Fernando Sansò (GPS Solutions, 2012)

On the combination of high-resolution and satellite-only global gravity models - Mirko Reguzzoni; Fernando Sansò (Journal of Geodesy, 2012)

Enhanced satellite positioning as a web service with goGPS open source software - Eugenio Realini; Daisuke Yoshida; Mirko Reguzzoni; Venkatesh Raghavan (Applied Geomatics, 2012)

First GOCE gravity field models derived by three different approaches - Roland Pail; Sean Bruinsma; Federica Migliaccio; Christoph Förste; Helmut Goiginger; Wolf-Dieter Schuh; Eduard Höck; Mirko Reguzzoni; Jan Martin Brockmann; Oleg Abrikosov; Martin Veicherts; Thomas Fecher; et al. (Journal of Geodesy, 2011)

On the combination of global and local data in collocation theory - Roland Pail; Mirko Reguzzoni; Fernando Sansó; Norbert Kühtreiber (Studia Geophysica et Geodaetica, 2010)

Optimal multi-step collocation: application to the space-wise approach for GOCE data analysis - Mirko Reguzzoni; Nikolaos Tselfes (Journal of Geodesy, 2009)

The Bayesian detection of discontinuities in a polynomial regression and its application to the cycle-slip problem - Maria Clara de Lacy; Mirko Reguzzoni; Fernando Sansò; Giovanna Venuti (Journal of Geodesy, 2008)